Rezidivrisiko nach thyreostatischer Behandlung immunogener und nicht-immunogener Hyperthyreosen - Voth, E.; Dickmann, N.; Schicha, H.; Emrich, D. (Nuklearmedizin - NuclearMedicine, 1990)
Data of 196 patients treated for hyperthyroidism exclusively with antithyroid drugs were analyzed retrospectively concerning the relapse rate within a follow-up period of four years. Patients were subdivided for primary or recurrent disease, and for immunogenic or non-immunogenic hyperthyroidism, respectively. In immunogenic as well as in non-immunogeriic hyperthyroidism, the relapse rate was significantly lower for patients with primary disease (35% and 52%, respectively) compared to those with recurrent hyperthyroidism (82%, p <0.001 and 83%, p <0.001, respectively). In patients with primary disease, clinical, biochemical and scintigraphic parameters were tested with respect to their capability of predicting a relapse. For immunogenic hyperthyroidism the highest relapse rates were observed in young patients and in those with large goitres, whereas for non-immunogenic hyperthyroidism they were highest in old patients, in those with nodular goitres and in those without an increased urinary iodine excretion at the time of diagnosing hyperthyroidism.